Assessing the influence of different post-harvest dormancy-breaking methods on the physicochemical characteristics of potato - Syed Mohsin Abbas; Raina Ijaz; Tanveer Hussain; Muhammad Nafees; Muhammad Wasim Haider; Alina-Stefania Stanciu; Ulkar İbrahimova (Postharvest Biology and Technology, 2026)

Socioeconomic drivers and farmers’ perception of climate change impact on agroforestry adoption: a regression-based study in South Punjab, Pakistan - Muhammad Safeer; Muhammad Zubair; Tanveer Hussain; Muhammad Ammar Khan; Muhammad Madnee; Turkan Hasanova Allahverdi (Agroforestry Systems, 2026)

Revisiting iron nutrition: a nano–organic approach for enhanced wheat yield, antioxidant resilience, and photosynthetic pigments - Hafiz Muhammad Jhanzab; Farhat Yasmeen; Ayshah Aysh Alrashidi; Muhammad Tanveer Altaf; Riaz Ahmad; Mohamed Ebaid; Ammar AL-Farga (Cereal Research Communications, 2026)

Harnessing biostimulants to alleviate potentially toxic element stress in vegetable crops - Amna Jamil; Waqas Liaqat; Asia Maqbool; Pramod Sargar; Muhammad Anwar-Ul-Haq; Shraddha Samindre; Muhammad Faheem Jan; Faheem Shehzad Baloch; Heba I. Mohamed; Muhammad Tanveer Altaf (Planta, 2026)

Sustainable approaches to alleviate salinity stress in two fenugreek cultivars through moringa leaf extract and salicylic acid - Sumreen Anjum; Iqra Tabassam; Mubeen Sarwar; Tanveer Hussain; Shoaib ur Rehman; Sumaira Maqsood; M. Irfan Ashraf; Muhammad Ashfaq; Qurban Ali (Plant Biosystems, 2026)

Edaravone dexborneol in acute ischemic stroke: a systematic review and meta-analysis of randomized trials with clinical and thrombectomy-specific subgroup analyses - Eman Tariq; Hooriya Ahmed; Tayyaba Ikram Qazi; Abdul Muhaimin; Aleena Amir Malik; Javeria Soomro; Rahimeen Qureshi; Zainab Murtaza; Sarum Ali Khan; Wajeeha Komal; Hadia Tanveer; Rida Ameer; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Transforming Banana Peel Waste into a Nano Biostimulant: Effects on Maize Seed Germination and Physio-Morphological Traits - Palwasha Sajjad; Umair Riaz; Azer Ahmadov; Tanveer-ul-Haq; Nazar Fareid; Faiza Hassan; Muhammad Adeel; Ayta Umar; Ren Maozhi; Muhammad Usman Aslam; Lamy Hamed (Journal of Plant Growth Regulation, 2026)

Elicitors in Plant Defense: Exploring Their Role in Biotic and Abiotic Stress Resistance - Muhammad Tanveer Altaf; Waqas Liaqat; Muhammad Aneeq Ur Rahman; Chidera Anuforo; Asia Maqbool; Amjad Ali; Muhammad Faheem Jan; Muhammad aasim; Heba I. Mohamed; Faheem Shehzad Baloch (Journal of Plant Growth Regulation, 2026)

Biochar Modification with Iron Oxide Nanoparticles can Enhance its Adsorption Capacity for Phosphorus - Sajeela Sehar; Muhammad Arif; Tanveer Ul Haq; Tanveer Ahmad; Muhammad Farooq Qayyum (Water, Air, & Soil Pollution, 2026)

Increased Atmospheric CO 2 Adversely Affects Large Pollinators, but Benefits Small Pollinators - Shahmshad Ahmed Khan; Muhammad Tanveer; Kit Prendergast; Taimoor Hussain; Arslan Shehryar; Asif Mehmood (Global Ecology and Biogeography, 2026)
Aim This study examines the impact of atmospheric CO 2 concentration on pollinator communities, focusing on body size‐related responses. It aims to understand how natural CO 2 variability influences pollinator abundance and diversity, and to assess potential ecological consequences for pollination services and ecosystem stability. Location The study was conducted across the Pothwar Plateau in Punjab, Pakistan, covering five districts: Murree, Rawalpindi/Islamabad, Jhelum, Chakwal and Attock. Time Period Field data were collected from September 2018 to May 2022, excluding December and January when pollinator activity was low. Major Taxa Studied The study focused on insect pollinators, including bees and hoverflies, and classified them into large‐ and small‐bodied groups based on size thresholds (e.g., bees were classified as large if their body length was ≥ 15 mm, and flies were classified as large if their body length was ≥ 10 mm). Methods A total of 25 study sites were randomly selected across an elevational gradient ranging from 350 to 2291 m. Atmospheric CO 2 concentrations were measured using a Temtop M2000 2nd digital meter at a standardized height of 1 m. Pollinator abundance and diversity were monitored using a transect‐based observation method (50 m transects, four per site). Sampling was conducted weekly from September to May, excluding December and January. Pollinators were identified in the field or collected for species‐level identification in the laboratory using morphological and image‐based techniques. Body size was measured using digital callipers. Statistical analyses were performed using Generalized Linear Mixed Models (GLMMs) to evaluate the relationship between pollinator populations, atmospheric CO 2 levels and other abiotic factors, while accounting for body size. Results A significant size‐dependent response to atmospheric CO 2 concentrations was observed. Larger‐bodied pollinators showed declines in abundance and diversity with increasing CO 2 levels, likely due to higher metabolic oxygen demands. In contrast, smaller‐bodied pollinators showed a positive association with elevated CO 2 concentrations. The relationship between CO 2 and pollinator communities remained consistent across different sites, confirming CO 2 as a reliable predictor variable. Main Conclusions Rising atmospheric CO 2 concentration could restructure pollinator communities by favouring smaller‐bodied species while negatively affecting larger‐bodied pollinators. This shift may have cascading effects on pollination networks and ecosystem stability. Conservation strategies should account for size‐specific vulnerabilities to climate‐induced CO 2 changes and prioritize protecting larger‐bodied pollinators, as they are more susceptible to CO 2 ‐related declines.

Genetic Diversity and Population Structure of 72 Turkish Ficus carica (L.) Genotypes Assessed Using SCoT Markers - Meliha Feryal Sarıkaya; Muhammad Azhar Nadeem; Sarmad Ali Qureshi; Mehmet Bedir; Muhammed Tatar; Amjad Ali; Muhammad Tanveer Altaf; Viyan Acar Uçer; Kağan Kökten; Erdal Aglar; Faheem Shehzad Baloch (Biochemical Genetics, 2026)

Dietary sodium propionate enhances growth performance, digestive enzymes, haematology and immunity in Wallago attu - Ayesha Tanveer; Noor Khan; Mahroze Fatima; Hafiz Abdullah Shakir; Ayesha Khizar; Syed Zakir Hussain Shah; Laiba Kareem; Saba Aftab; Malik Muhammad Ramzan; Ahmed Mustafa; Simon John Davies (Journal of Fish Biology, 2026)
Sodium propionate (SP), a short‐chain fatty acid, has been widely used as a feed additive to improve fish growth and health status. The current experiment was designed to investigate the effects of dietary SP on growth, enzymatic activities, haematology and immune status of Wallago attu . Fingerlings (initial weight = 8.80 ± 0.58 g) were fed with graded levels of SP comprising 0.0, 0.5, 1.0, 2.0, 4.0 and 8.0 g/kg levels for 60 days in triplicate glass aquaria (89 × 58 × 61 cm [length × width × depth]). The results showed significant ( p W. attu fingerlings when fed with graded levels of SP. In conclusion, the SP supplementation in W. attu showed best results ranged between 2 and 4 g/kg level by improving fish health and growth performance.

Nanoparticles in Vegetable Production: From Soil to Human Health - Amna Jamil; Muhammad Tanveer Altaf; Ishtiaq Ahmad; Waqas Liaqat; Asia Maqbool; Muhammad Anwar-Ul-Haq; Pramod Sargar; Heba I. Mohamed; Faheem Shehzad Baloch (Water, Air, & Soil Pollution, 2026)

Flash flood susceptibility assessment using an integrated geomorphologic framework in data-scarce arid and semi-arid regions - Aftab Ullah; Rashid Farooq; Abdul Razzaq Ghumman; Muhammad Ejaz Tanveer; Muhammad Atiq Ur Rehman Tariq (Modeling Earth Systems and Environment, 2026)
Flash floods are among the most frequent natural hazards, posing serious environmental challenges, particularly in arid and semi-arid regions where steep topography and compact basin morphometry accelerate surface runoff. The ungauged hill torrents of southwestern Punjab, Pakistan, are particularly vulnerable to such events, experiencing recurrent, intense flash floods. This study develops an integrated GIS-based morphometric framework to assess flash flood susceptibility across 13 major hill torrents in DG Khan and Rajanpur, Punjab. Fifteen morphometric parameters were analyzed using three complementary approaches: Hazard Degree (HD), Principal Component Analysis (PCA), and Analytical Hierarchy Process (AHP). The HD method captured the cumulative influence of all parameters. At the same time, PCA reduced redundancy and identified four dominant controlling factors: length of overland flow (Lo), form factor (Ff), circulatory ratio (Rc), and ruggedness number (Rn). The AHP further incorporated expert judgment, identifying drainage density (Dd) and ruggedness number as the most influential parameters, followed by basin relief (Bh) and drainage frequency (Fs). The convergence of results across the three independent methods significantly improves classification reliability compared to single-method analyses. Three hill torrents (Vidore, Mithawan, and Kaha) were consistently classified as highly susceptible, one as moderately susceptible, and four as low susceptibility. Hence, the proposed integrated HD-PCA-AHP model reduces methodological uncertainty and provides a transferable, data-efficient tool for assessing flash flood susceptibility and managing watersheds in data-scarce arid and semi-arid regions.

Leveraging Extremophyte Adaptations as a Roadmap for Crop Design for Arid Lands - Mohsin Tanveer; Lei Wang; Hamza Tariq; Muhammad Talha Ramzan; Alisdair R. Fernie; Jaume Flexas; Sergey Shabala; Josep Peñuelas (Global Change Biology, 2026)
Anthropogenic climate change is driving a convergence of rapid soil aridification and secondary salinization that threatens to degrade over half of the world's arable land. As conventional glycophytic crops reach their physiological limits, global food security depends on decoding the evolutionary adaptations of extremophytes. This review synthesizes the functional traits and ecosystem‐level impacts of extremophytes, the native flora of these marginal environments, and evaluates their potential as a biophysical buffer against land degradation. Here, we identify two cornerstone strategies that allow these plants to thrive where others fail: (i) the precise spatiotemporal orchestration of reactive oxygen species (ROS) as critical signaling molecules for developmental plasticity; and (ii) the active recruitment of stress‐protective microbiomes via targeted exudation, effectively transforming barren soil into a functional ecosystem. We argue that integrating extremophytes into diversified agroecosystems, through intercropping, phytoremediation rotations, and circular bioeconomy models, offers quantifiable results to enhance ecosystem multifunctionality and sustainably intensify production on degrading lands. By bridging profound mechanistic discovery with ecological engineering, this perspective provides an actionable plan for translating extremophyte biology into crops capable of withstanding a drier future.

Hypoxia adaptation in yak: Molecular, Genetic, and Physiological mechanisms of high-altitude resilience - Muhammad Wasique Shahid; Hammad Qaiser; Tanveer Hussain (Livestock Science, 2026)

A comprehensive review on nutritional, functional, and clinical perspectives of chia seeds and chia mucilage - Muhammad Arham Rauf; Maira Abdul Razzak; Fatima Waheed; Tabana Naz; Maham Fatima; Tanveer Ahmad; Muhammad Arslan; Usman Mir Khan; Mian Kamran Sharif (Bioactive Carbohydrates and Dietary Fibre, 2026)

Synergistic Degradation and Cytotoxicity Mitigation of Meloxicam Using UV/Perovskite/H₂O₂ and Gamma/H₂O₂: A Comparative Study - Muhammad Asad Khan; Mohamed A. Habib; Muhammad Imran Kanjal; Majid Muneer; Muhammad Asghar Jamal; Tanveer Hussain Bokhari; Usman Irshad; Ahmed B. M. Ibrahim (Water, Air, & Soil Pollution, 2026)

Photo-activated defect engineering unlocks high-performance proton transport in garnet electrolytes - Bushra Bibi; Atif Nazar; Muhammad Yousaf; Tanveer Farid; Rizwan Raza; Syed Asad Abbas Bukhari; Muhammad Faisal Anawar; Kashif Nazar; Hafsa Mansha; Yuzheng Lu; Bin Zhu (Chemical Engineering Journal, 2026)

Retraction Note: Optimizing callogenesis in five potential medicinal herbs for the bioactive constituents: a sustainable approach to pharmaceutical production - Muhammad Wasim Haider; Muhammad Nafees; Maryyam Bint-e-Tariq; Umar Farooq; Tanveer Hussain; Taki Demir; Asad Masood; Muhammad Samsam Raza; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Ozhan Simsek; Temoor Ahmed; et al. (Genetic Resources and Crop Evolution, 2026)

Retraction Note: Salinity effects on growth, biomass production, and genetic resources for phytoremediation potential of halophyte species in the desert - Muhammad Abid; Muhammad Rafay; Tanveer Hussain; Muhammad Azeem Sabir; Muneeb Khalid; Muhammad Madnee; Hussain Ahmed Makki; Muhammad Qasim; Ehab I. Taha; Mounir M. Bekhit; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Closed-loop processing of in-situ modified wood: Biopolymer-structure-property relationships - Tanveer Farid; Kashif Abbass; Lev A. Trusov; Boris P. Gorshunov; Evgeny A. Gorbachev; Saghir Hussain; Muhammad Naeem Ashiq; Yike Li; Muhammad Imran Asghar; Shukui Li; Hongyi Liu; Jing Yu; et al. (Carbohydrate Polymers, 2026)

Isolation and molecular characterization of plant growth-promoting rhizobacteria for biocontrol of Fusarium head blight in wheat - Syed Jehangir Shah; Somaira Bibi; Safira Attacha; Syed Tanveer Shah; Noreen Asim; Waqas Ahmad; Muhammad Sayyar Khan; Ishrat Naz; Muhammad Ibrahim; Aftab Jamal (Cereal Research Communications, 2026)

Simultaneous quantification of hydroxycinnamate derivatives and antioxidant activity of Ziziphus oxyphylla Edgew. leaf methanolic extract - Surriya Naheed; Muhammad Wajid; Afsheen Ehsan; Khalid Hussain; Gulzar Muhammad; Naureen Shehzadi; Muhammad Tanveer Khan; Imran Ahmad; Adnan Ashraf (Natural Product Research, 2026)

Synergistic NiO-Pt heterostructure for enhanced hydrogen evolution: Boosting charge transfer and catalytic efficiency in alkaline media - Faria Rafique; Shahzad Ameen; Muhammad Hammad Ali; Aleena Tahir; Hamayal Shahzad; Amina Bhatti; Tanveer ul Haq; Mira Tul Zubaida Butt; Ammar Ahmed Khan; Saleh A. Ahmed; Irshad Hussain; Habib Ur Rehman (Fuel, 2026)

Synergistic Role of Plant Growth-Promoting Rhizobacteria and Zinc Ferrite Nanoparticles in Mitigating Mercury Stress in Chickpea (Cicer arietinum L.) - Waqar Younas; Hina Khan; Humera Amin; Sami Ullah; Abd Ullah; Usman Ali; Muhammad Nafees; Fazal Amin; Iftikhar Ahmed; Tanveer Hussain; Mohamed Taha Yassin; Rashid Iqbal (Water, Air, & Soil Pollution, 2026)

Tissue-specific Ca2+ profiles associated with differential Ca2+ signalling and salinity stress tolerance between quinoa and spinach - Mohsin Tanveer; Waqas ud Din Khan; Muhammad Obeid Alshaharni; Caroline Ivsic; Zhong-Hua Chen; Lei Wang; Sergey Shabala (Plant and Soil, 2026)

Eco-Friendly Gum Arabic–Essential Oil Coatings for Decay Control and Quality Preservation of Pomegranate Fruit During Storage - Muhammad Waqar Alam; Sumreen Anjum; Mubeen Sarwar; Adnan Mukhtar; Akhtar Hameed; Tanveer Hussain; Tauhid Iqbal (Applied Fruit Science, 2026)

Unveiling the impact of green technological innovation and foreign remittances on greenhouse gas emissions: A path to sustainable development in India - Muhammad Israr; Huaming Song; Arsalan Tanveer; Daud Abdul; Kashif Abbass (Environment, Development and Sustainability, 2026)

Retraction notice to “Almond shell-derived biochar decreased toxic metals bioavailability and uptake by tomato and enhanced the antioxidant system and microbial community” [Sci. Total Environ. 929 (2024) 172632] - Muhammad Imran Ghani; Mohammad Abass Ahanger; Tanveer Ali Sial; Sajjad Haider; Junaid Ali Siddique; Ruidong Fan; Yanjiang Liu; Esmat F. Ali; Manish Kumar; Xing Yang; Jörg Rinklebe; Xiaoyulong Chen; et al. (Science of The Total Environment, 2026)

Copper homeostasis: Crosstalk with plant secondary metabolism and stress responses - Muhammad Tanveer Akhtar; Zhaogeng Lu; Shi-xiong Ren; He-lin Zou; Iqra Noor; Biao Jin (Plant Science, 2026)

Unveiling the charge transfer pathways in CuWO4/NiFe/SnWO4 coupled S-scheme heterojunction for photocatalytic dye degradation - Rimsha Aqeel; Tanveer Hussain Bokhari; Saqib Javaid; Amina Zafar; Muhammad Inayat Ullah; Muhammad Tariq Nadeem; Atia Khalid; Shafqat Karim; Ting Zhu; Amjad Nisar; Mashkoor Ahmad (Journal of Water Process Engineering, 2026)

Performance of novel media-based aquaponics under stress of different antibiotics: Role of biochar and zero-valent iron - Muhammad Tanveer; Chengkai Fu; Linlan Zhuang; Yanhui Zhao; Doinglin Wang; Peihan Yu; Yiqiao Zhang; Zhen Hu (Journal of Hazardous Materials, 2026)

A comprehensive insight on the bioactive phytochemicals and pharmacological propensities of Ficus benghalensis L.: a reservoir for modern drug discovery - Sulaman Yaqub; Muhammad Islam; Hamid Saeed; Abrar Ahmad; Khurram Aamir; Rida Naeem; Meerab Tanveer (Phytochemistry Reviews, 2026)

Photo-mediated synthesis of Ag/ZnO Nanocomposite: A sustainable green approach for enhanced hydrogen production and photocatalytic degradation - Asif Khalil; Muhammad Zia Ur Rehman Faurooqi; Maryam Khalid; Tanveer Farid; Saghir Hussain; Khalid Mahmood (Fuel, 2025)

Comparative analysis of Apocynum pictum and Apocynum venetum honey: identify with nutritional and health-promoting metabolites - Zeeshan Ali Buttar; Jiyun Ma; Lei Wang; Muhammad Rizwan Shoukat; Wei Ren; Li Jiang; Mohsin Tanveer (Food Chemistry, 2025)

Valorization of fruit and vegetable by-products for protein extraction and their functional applications in food and non-food sectors - Laiba Khalid; Ifrah Jabeen; Tanveer Ahmad; Muhammad Inam-ur-Raheem; Arashi Shahid; Teresa Cirillo; Francesco Esposito (Food and Bioproducts Processing, 2025)

Double-layer stratification of Cross fluid flow with viscous dissipation and variable thermal conductivity - T. Salahuddin; A. Maqsood; Muhammad Awais; Mair Khan; Anum Tanveer; Samia Elattar (Dynamics of Atmospheres and Oceans, 2025)

Mapping the non-coding RNA landscape in ataxia telangiectasia: a scoping review of ATM dependent miRNA and lncRNA dysregulation - Muhammad Junaid Iqbal; Usman Ameen; Hamza Tanveer; Laraib Israr; Anastasia Ricci; Gianluca Morganti; Muhammad Jawad Khan; Michele Menotta (Molecular Biology Reports, 2025)
Ataxia-Telangiectasia (A-T) is caused by biallelic Ataxia-Telangiectasia Mutated (ATM) protein mutations and is hallmarked by neurodegeneration, immunodeficiency and cancer susceptibility. Emerging work suggests that non-coding RNAs are integral to the ATM driven DNA damage response, yet the scope of non-coding RNA perturbation in A-T has not systematically mapped. This study is done to chart and synthesize all primary evidence on ncRNA dysregulation in A-T and to identify mechanistic gaps and research priorities. The evidence base comprises a total of five studies focused exclusively on microRNAs and long non-coding RNAs. Baseline sequencing of 20 patients revealed consistent downregulation of miR-195-5p, miR-30a-5p and miR-342-3p. Low dose γ-irradiation of ATM-null lymphoblastoid cell lines produced an exaggerated bidirectional shift (8 microRNAs upregulated, 6 downregulated) versus wild-type, whereas primary T-cells showed largely ATM independent rises of miR-34a-5p and miR-182-5p. A lymphoblastoid cell lines study distinguished 22 recessive or dominant radiation-responsive microRNAs. Long non-coding RNAs profiling identified 149 transcripts that require functional ATM for induction and three uniquely upregulated in A-T cells. No circular RNA study in A-T is observed till date. The ncRNA research in A-T is nascent with five studies present a miRNA dysregulation and an ATM-dependent lncRNA surge that is lost in A-T, but leave circRNAs, neuronal tissues and functional validation unexplored. Intermediate dose stress models, total and small RNA-seq under DNA damage and oxidative stress, and CRISPR rescue/knockout screens in patient derived organoids are immediate priorities for exploring the role of ncRNAs as therapeutic targets in A-T.

Unveiling genetic diversity and population structure in lentil (Lens culinaris) germplasm through scot markers - Sarmad Ali Qureshi; Muhammad Azhar Nadeem; Meliha Feryal Sarıkaya; Amjad Ali; Muhammed Tatar; Muhammad Tanveer Altafl; Dilek Tekdal; Muhammad Kashif Ilyas; Seyithan Seydoşoğşu; Sezai Ercişli; Kağan Kökten; Faheem Shahzad Baloch (Molecular Biology Reports, 2025)

From global challenges to specific solutions: climate change impacts on agriculture with a focus on sorghum through bibliometric analysis - Waqas Liaqat; Muhammad Tanveer Altaf; Muhammad Faheem Jan; Haseeb Ahmad; Ehtisham Hassan Khan; Celaleddin Barutçular; Gönül Cömertpay; Faheem Shehzad Baloch; Heba I. Mohamed (Cereal Research Communications, 2025)

Climatic variability linkages with agroforestry adoption in Pakistan: a socio-ecological review - Muhammad Safeer; Muhammad Zubair; Tanveer Hussain; Muhammad Ammar Khan; Muhammad Madnee (Agroforestry Systems, 2025)

Navigating the asymmetric influence of smart grid technology, renewable energy and institutional quality toward a sustainable environment - Daud Abdul; Jiang Wenqi; Arsalan Tanveer; Muhammad Faheem (Environment, Development and Sustainability, 2025)

Endophytic fungi as biocontrol agents: A metabolite-driven approach to crop protection and sustainable agriculture - Muhammad Faiq; Amjad Ali; Shazia Shafique; Sobiya Shafique; Allah Rakha Yaseen; Rimsha Fatima; Muhammad Tanveer Altaf; Faheem Shehzad Baloch (Physiological and Molecular Plant Pathology, 2025)

Next-generation strategies for nitrogen-efficient maize production for a greener tomorrow - Muhammad Faheem Jan; Waqas Liaqat; Muhammad Tanveer Altaf; Muhammad Dawood Ahmadzai; Asia Maqbool; Faheem Shehzad Baloch; Ming Li (Field Crops Research, 2025)

Systematic review of the microbiological status of farmed and processed Tenebrio molitor: Insights on foodborne pathogens in food and feed applications - Xin Yan; Lenaïg Brulé; Muhammad Tanveer Munir; Michel Federighi; Jean-Michel Cappelier; Vanessa Jury; Boris Misery; Géraldine Boué (Food Control, 2025)

Comprehensive ampelographic and biochemical profiling of exotic grapevine (Vitis vinifera L.) cultivars grown under semi-arid conditions - Ubaid Abdul Khaliq; Irfan Ali; Abdel‑Halim Ghazy; Muhammad Tahir Akram; Mahmood-ul-Hassan; Haider Ali; Umer Habib; Tanveer Hussain; Kotb A. Attia; Sajid Fiaz; Abdullah A. Al-Doss; Muhammad Uzair; et al. (Genetic Resources and Crop Evolution, 2025)

Assessment of plant community composition and diversity across cemeteries: indicator species of burial sites in Tehsil Samahni, Azad Kashmir, Pakistan - Zel E Arooj; Muhammad Ishtiaq; Muhammad Waqas Mazhar; Mehwish Maqbool; Tanveer Hussain (Community Ecology, 2025)

N-acetylcysteine as a feed additive to counteract ochratoxin A toxicity in poultry - Muntaha Tanveer; Muhammad Imran; Muhammad Kashif Saleemi; Mubashar Shareef; Muhammad Imran; Saqib Umar (Food Additives & Contaminants: Part A, 2025)

Do financial inclusion and green growth matter for environmental sustainability? A fresh insight through nonlinear model - Muhammad Sajid; Muhammad Akbar Ali Ansari; Arsalan Tanveer; Noreen Safdar; Muhammad Faheem (Clean Technologies and Environmental Policy, 2025)

Development and characterisation of buccal dispersible film, syrup and effervescent granules of extemporaneous antigout remedy - Ayisha Shaukat; Khalid Hussain; Naureen Shehzadi; Muhammad Tanveer Khan; Siddiqa Perveen; Nadeem Irfan Bukhari (Natural Product Research, 2025)

Recent advancements in chemometrics based non-destructive analytical techniques for rapid detection of adulterants in milk and dairy products – A review - Rui Xu; Muhammad Zeeshan Adil; Sidra Jabeen; Khansa; Mahwish Tanveer; Sadia Younis; Bakhtawar Shafique; Long Li (Food Control, 2025)

Corrigendum to “Dual-modification strategy for efficient inverted perovskite solar cells via thermally induced liquid crystals and boosting of phenethylammonium by carbazole” [Chem. Eng. J. 516 (2025) 163918] - Bilal Mehmood; Chen Zhang; Shan Wu; Jiangying Lu; Xu Zheng; Wei Jiang; Kamran Amin; Shudi Lu; Muhammad Iftikhar Khan; Muhammad Sultan; Tanveer Ashraf; Zhijie Wang; et al. (Chemical Engineering Journal, 2025)

Approaches for the amelioration of adverse effects of drought stress on soybean plants: from physiological responses to agronomical, molecular, and cutting-edge technologies - Muhammad Faheem Jan; Muhammad Tanveer Altaf; Waqas Liaqat; Changzhuang Liu; Heba I. Mohamed; Ming Li (Plant and Soil, 2025)

Cyto-genotoxic assessment of bisphenol P through expression of DNA damage/repair genes in MDBK cell line - Muhammad Muddassir Ali; Samra Afzal; Maryam Javed; Imran Rashid; Furqan Awan; Asad Ullah; Tanveer Majeed; Hadeer Darwish; Ahmed Noureldeen; Jawaher Albaqami; Khalid Mehmood (In Vitro Cellular & Developmental Biology - Animal, 2025)

Genome-wide analysis of the UFGT gene family in colored cotton: evolution, structure and expression patterns - Jaweria Iqbal; Muhammad Tanveer Altaf; Waqas Malik; Abdul Qayyum (Genetic Resources and Crop Evolution, 2025)

Assessing Human-Wildlife Conflict in Lakki Marwat, Pakistan: Economic Impacts and People’s Perceptions - Tanveer Khan; Shakeel Ahmad; Tahir Mehmood; Sajjad Rais Khan; Daulat Ullah Khan; Salman Khan; Muhammad Ullah; Ejaz Rahim (European Journal of Wildlife Research, 2025)

Dual-modification strategy for efficient inverted perovskite solar cells via thermally induced liquid crystals and boosting of phenethylammonium by carbazole - Bilal Mehmood; Chen Zhang; Shan Wu; Jiangying Lu; Xu Zheng; Wei Jiang; Kamran Amin; Shudi Lu; Muhammad Iftikhar Khan; Muhammad Sultan; Tanveer Ashraf; Zhijie Wang; et al. (Chemical Engineering Journal, 2025)

In-vitro assessment of probiotic potential of bacteria isolated from chicken gastrointestinal tract - Fatima Shahbaz; Fatima Muccee; Afreen Fatima Mirza; Muhammad Abdullah Tanveer; Amal H. I. Al Haddad; Nadia Hussain (Antonie van Leeuwenhoek, 2025)

Exploring genetic diversity of Turkish fig (Ficus carica L.) germplasm using inter-Primer Binding Site (iPBS) retrotransposon markers - Viyan Acar Uçer; Erdal Aglar; Parnaz Mortazavi; Sarmad Ali Qureshi; Amjad Ali; Muhammed Tatar; Muhammad Tanveer Altaf; Mehmet Bedir; Sezai Ercişli; Muhammad Azhar Nadeem; Faheem Shehzad Baloch (Genetic Resources and Crop Evolution, 2025)

Chlorophyll fluorescence: a smart tool for maize improvement - Muhammad Faheem Jan; Ming Li; Waqas Liaqat; Muhammad Tanveer Altaf; Changzhuang Liu; Haseeb Ahmad; Ehtisham Hassan Khan; Zain Ali; Celaleddin Barutçular; Heba I. Mohamed (Cereal Research Communications, 2025)

Revealing Effects of Calcium-Based Formulations Focusing on Membrane Instability, Fruit Quality, Phytochemical Properties, and Disease Incidence in Peach (Prunus Persica) During Storage - Syed Tanveer Shah; Muhammad Sajid; Abdul Basit; Bibi Haleema; Ayesha Khan; Heba I. Mohamed (Applied Fruit Science, 2025)

Evidencing the socioeconomic impact of agroforestry in an arid climate: a case study of district Bahawalpur, Punjab, Pakistan - Muhammad Madnee; Tanveer Hussain; Muhammad Abid; Muneeb Khalid; Hussain Ahmed Makki; Nugraha Akbar Nurrochmat; Mahmuod Abubakar Bashir (Agroforestry Systems, 2025)

Ostrich oil evaluation; Parallel to food and pharmaceutical industries requirements: A review - Shehnshah Zafar; Adnan Amjad; Muhammad Tauseef Sultan; Muhammad Mueed Tanveer Malik (Food and Humanity, 2025)

From pollution to preservation: a dynamic examination of tourism, globalization, and environmental resilience in top-tier economies - Xudan Zheng; Mo Kuang; Muhammad Faheem; Arsalan Tanveer (Clean Technologies and Environmental Policy, 2025)

Enhancing defense and production efficiency in rainbow trout (Oncorhynchus mykiss) through prophylactic dietary selenium and vitamin E fortification - Said Jasim Shah; Noor Khan; Mahroze Fatima; Sheeza Bano; Ayesha Tanveer; Sadia Nazir; Muhammad Asghar; Ahmed Mustafa; Maryam Tahir; Saba Aftab; Alex Hing Leung Wan; Simon John Davies (Animal Feed Science and Technology, 2025)

Mathematical study of infectious disease of pines caused by bark beetles - Takasar Hussain; Muhammad Ozair; Adnan Aslam; Maham Afaq; Muhammad Tanveer; Muhammad Awais; J. F. Gómez-Aguilar (Modeling Earth Systems and Environment, 2025)

Advancing Chickpea Breeding: Omics Insights for Targeted Abiotic Stress Mitigation and Genetic Enhancement - Muhammad Tanveer Altaf; Waqas Liaqat; Amjad Ali; Amna Jamil; Muhammad Fahad; Muhammad Aneeq Ur Rahman; Faheem Shehzad Baloch; Heba I. Mohamed (Biochemical Genetics, 2025)

Fish oil replacement with linseed oil affects growth, tissue fatty acid composition, blood chemistry, and antioxidant biomarkers in rohu, Labeo rohita - Muhammad Asghar; Noor Khan; Mahroze Fatima; Seyda Tacer-Tanas; Simon John Davies; Naveed ul Haque; Ayesha Tanveer; Murat Arslan (Aquaculture International, 2025)

Differential responses of leguminous tree species to drought stress: implications for agroforestry and restoration in arid and semi-arid climates - Muhammad Madnee; Tanveer Hussain; Muhammad Azeem Sabir; Muhammad Abid; Muneeb Khalid; Hussain Ahmad Makki; Sajjad Ali; Nugraha Akbar Nurrochmat (Agroforestry Systems, 2025)

Molecular screening of diverse Tomato germplasm for root-knot nematode resistance using the Mi23 marker - Parnaz Mortazavi; Amjad Ali; Muhammed Tatar; Fatih Ölmez; Muhammad Tanveer Altaf; Muhammad Azhar Nadeem; Hayriye Yildiz Dasgan; Boran Ikiz; Tuğçe Temtek; Ömer Faruk Bilgin; Ayşe Mücahitoğlu; Mahmut Bayram; et al. (Physiological and Molecular Plant Pathology, 2025)

RETRACTED ARTICLE: Salinity effects on growth, biomass production, and genetic resources for phytoremediation potential of halophyte species in the desert - Muhammad Abid; Muhammad Rafay; Tanveer Hussain; Muhammad Azeem Sabir; Muneeb Khalid; Muhammad Madnee; Hussain Ahmed Makki; Muhammad Qasim; Ehab I. Taha; Mounir M. Bekhit; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

RETRACTED ARTICLE: Optimizing callogenesis in five potential medicinal herbs for the bioactive constituents: a sustainable approach to pharmaceutical production - Muhammad Wasim Haider; Muhammad Nafees; Maryyam Bint-e-Tariq; Umar Farooq; Tanveer Hussain; Taki Demir; Asad Masood; Muhammad Samsam Raza; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Ozhan Simsek; Temoor Ahmed; et al. (Genetic Resources and Crop Evolution, 2025)

The dynamic role of income inequality, renewable energy and risk components towards environmental sustainability: fresh insights through CS-ARDL approach - Muhammad Asif Khan; Daud Abdul; Wenping Wang; Arsalan Tanveer; Muhammad Faheem; Taimoor Hassan (Environment, Development and Sustainability, 2025)

Enhancement of nitrogen transformation in media-based aquaponics systems using biochar and zerovalent iron - Muhammad Tanveer; Shuo Wang; Xiaolong Ma; Piehan Yu; Peipei Xu; Linlan Zhuang; Zhen Hu (Bioresource Technology, 2025)

Development of tetraploids in tissue culture: modern techniques and biotechnological innovations - Sabeen Rehman Soomro; Salma Naimatullha Soomro; Muhammad Tanveer Altaf; Waqas Liaqat; Muhammad Azhar Nadeem; Faheem Shehzad Baloch; Muhammad Aasim; Heba I. Mohamed (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Disease resistance to tomato yellow leaf curl virus (TYLCV) enhanced by natural plant growth regulators and biopesticide - Sajid Mehmood; Marina Sajid; Tamsal Murtaza; Tanveer Hussain; Rana Naveed Ur Rehman; Muhammad Tahir Akram; Huma Abbas; Khadija Rafiq; Muhammad Kamran; Manzoor Hussain; Muhammad Inam ul Haq; Gull-e-laala Khan (Journal of Plant Diseases and Protection, 2025)

Moringa Biopriming with Zn Spray Improved Nutrients Rich Biofortified Chickpea Grains and Drought Tolerance at Reproductive Stages Under Arid Environment - Hamid Nawaz; Malik Muhammad Yousaf; Nazim Hussain; Tanveer Hussain; Malik Waqar Yousaf; Malik Ibrar Yousaf; Mona S. Alwahibi; Mohamed S. Elshikh; Baber Ali; Rashid Iqbal (Journal of Crop Health, 2025)

Impact of socioeconomic and sociopolitical factors on environmental sustainability in Pakistan - Shehla Ambreen; Ma Wenbao; Wali Muhammad Khoso; Tanveer Ahmed Mangi; Zulfiqar Ali Baloch (Environment, Development and Sustainability, 2025)

Applicability of Start Codon Targeted (SCoT) markers for the assessment of genetic diversity in bread wheat germplasm - Muhammad Tanveer Altaf; Muhammad Azhar Nadeem; Amjad Ali; Waqas Liaqat; Mehmet Bedir; Nurettin Baran; Aleksandra Ilić; Muhammad Kashif Ilyas; Abdul Ghafoor; Hamide Dogan; Muhammad Aasim; Faheem Shehzad Baloch (Genetic Resources and Crop Evolution, 2025)
Research endeavors focused on examining genetic diversity play a pivotal role in advancing agricultural practices, as they furnish valuable insights for breeding programs and the preservation of germplasm. Wheat holds significant global importance as a cereal crop, serving as a primary source of sustenance for almost one-third of the global human population. In the current study, a total of 80 bread wheat genotypes were characterized using the start codon targeted (SCoT) marker system. A set of 14 polymorphic primers yielded a cumulative count of 399 bands with an average of 28.05 bands per primer. The range of diversity markers, such as polymorphism information content (0.26–0.59), effective numbers of alleles (1.27–1.59), Shannon’s information index (0.30–0.51), and gene diversity (0.18–0.34), provided evidence of elevated genetic differences within the examined germplasm. According to the findings of the molecular variance analysis, greater genetic variations are found within populations (92%). The model-based structural approach partitioned the 80 bread wheat genotypes into two distinct populations (Population A and B). The diversity indices based on the structures of the populations revealed that population A had greater diversity compared to population B. Both the principal coordinate analysis and the neighbor-joining analysis also differentiated the 80 different bread wheat genotypes based on their respective collection points. The present crop diversity offers great opportunities for enhancing crop quality and increasing tolerance to environmental challenges, both of which will lead to a reduction in the problem of food insecurity.

From stress to resilience: Unraveling the molecular mechanisms of cadmium toxicity, detoxification and tolerance in plants - Iqra Noor; Hamza Sohail; Muhammad Tanveer Akhtar; Jiawen Cui; Zhaogeng Lu; Salma Mostafa; Mirza Hasanuzzaman; Sajjad Hussain; Nan Guo; Biao Jin (Science of The Total Environment, 2024)

Sentry eyes? Women directors and corporate penalties - Muhammad Azeem Qureshi; Ammar Ali Gull; Tanveer Ahsan (Journal of Cleaner Production, 2024)

Applicability of SCoT markers in unraveling genetic variation and population structure among sugar beet (Beta vulgaris L.) germplasm - Nazlı Aybar Yalinkiliç; Sema Başbağ; Muhammad Tanveer Altaf; Amjad Ali; Muhammad Azhar Nadeem; Faheem Shehzad Baloch (Molecular Biology Reports, 2024)

A novel homozygous missense TTC12 variant identified in an infertile Pakistani man with severe oligoasthenoteratozoospermia and primary ciliary dyskinesia - Imtiaz Ali; Haider Ali; Ahsanullah Unar; Fazal Rahim; Khalid Khan; Sobia Dil; Tanveer Abbas; Ansar Hussain; Aurang Zeb; Muhammad Zubair; Huan Zhang; Hui Ma; et al. (Molecular Genetics and Genomics, 2024)

In Silico Identification and Characterization of Rare Cold Inducible 2 (RCI2) Gene Family in Cotton - Muhammad Fahad; Leeza Tariq; Muhammad Tanveer Altaf; Muhammad Shahnawaz; Mudassir Aslam; Waqas Liaqat; Inayat Ullah; Izhar Ullah; Heba I. Mohamed; Abdul Basit (Biochemical Genetics, 2024)

Biochemical analysis and fertilization success of Cirrhinus mrigala ova during induced spawning - Shahid Sherzada; Tanveer Ahmad; Saeed Akram Khan; Muhammad Inayat; Sohail Ahmad; Abdur Rahman (Animal Reproduction Science, 2024)

A thorough overview of the literature on waste recycling in the circular economy: current practices and future perspectives - Muhammad Tabish; Syed Abdul Rehman Khan; Zhang Yu; Muhammad Tanveer (Environmental Science and Pollution Research, 2024)

Valorization of poultry slaughter wastes via extraction of three structural proteins (gelatin, collagen and keratin): A sustainable approach for circular economy - Muhammad Talha; Muhammad Tanveer; Aqsa Abid; Abid Aslam Maan; Muhammad Kashif Iqbal Khan; Hira Shair; Nimra Tanveer; Almas Mustafa (Trends in Food Science & Technology, 2024)

Effect of the polyelectrolyte multilayers' charge on water splitting, fluxes of ions, selectivities and current efficiencies in ion transport through membranes - Muhammad Ahmad; Mahmood Ahmed; Abid Ali; Tanveer A. Wani; Khuram Khalid; Ijaz Ali (Desalination, 2024)

Strategies and bibliometric analysis of legumes biofortification to address malnutrition - Muhammad Tanveer Altaf; Waqas Liaqat; Amna Jamil; Muhammad Faheem Jan; Faheem Shehzad Baloch; Celaleddin Barutçular; Muhammad Azhar Nadeem; Heba I. Mohamed (Planta, 2024)

Appraisal of potentially toxic metals contamination in protein supplements for muscle growth: A chemometric approach and associated human health risks - Misbah Irshad; Mahmood Ahmed; Muhammad Ramzan; Mehreen Fatima; Fatima Aftab; Mudassar Sanaullah; Shaista Qamar; Zohaib Iftikhar; Tanveer A. Wani; Seema Zargar (Journal of Trace Elements in Medicine and Biology, 2024)

A Bibliometric Analysis of Genome-wide Association Study (GWAS) and Sorghum (Sorghum bicolor L) Based on Web of Science Using VOS Viewer - Muhammad Tanveer Altaf; Waqas Liaqat; Amna Jamil; Muhammad Faheem Jan; Faheem Shehzad Baloch; Heba I. Mohamed (Journal of Soil Science and Plant Nutrition, 2024)

A Critical Review: Breeding Objectives, Genomic Resources, and Marker-Assisted Methods in Sorghum (Sorghum bicolor L.) - Muhammad Tanveer Altaf; Waqas Liaqat; Amna Jamil; Heba I. Mohamed; Muhammad Fahad; Muhammad Faheem Jan; Faheem Shehzad Baloch (Journal of Soil Science and Plant Nutrition, 2024)

Exogenous Application of Silicon and Zinc Attenuates Drought Tolerance in Eruca sativa L. Through Increasing Chlorophyll Pigments, Osmoprotectants, and Modulating Defense Mechanisms - Iqbal Hussain; Atif Ayub; Airish Nayab; Muhammad Arslan Ashraf; Muhammad Arslan Ashraf; Sadam Hussain; Manzer H. Siddiqui; Muhammad Azeem Sabir; Usman Zulfiqar; Tanveer Hussain Khan (Journal of Plant Growth Regulation, 2024)

Role of reactive nitrogen species in changing climate and future concerns of environmental sustainability - Muhammad Rizwan; Hurain Tanveer; Muhammad Hayder Ali; Muhammad Sanaullah; Abdul Wakeel (Environmental Science and Pollution Research, 2024)

Assessment of carcinogenic and non-carcinogenic risk of exposure to potentially toxic elements in tea infusions: Determination by ICP-OES and multivariate statistical data analysis - Mahmood Ahmed; Muhammad Ahmad; Muhammad Ayyan Khan; Aamir Sohail; Mudassar Sanaullah; Waqar Ahmad; Dure Najaf Iqbal; Khuram Khalid; Tanveer A. Wani; Seema Zargar (Journal of Trace Elements in Medicine and Biology, 2024)

Characteristics and mechanisms of phosphine production in sulfur-based constructed wetlands - Shuo Wang; Haodong Hu; Muhammad Tanveer; Mingde Ji; Weiqiang Chai; Haiming Wu; Huijun Xie; Zhen Hu (Water Research, 2024)

RETRACTED: Almond shell-derived biochar decreased toxic metals bioavailability and uptake by tomato and enhanced the antioxidant system and microbial community - Muhammad Imran Ghani; Mohammad Abass Ahanger; Tanveer Ali Sial; Sajjad Haider; Junaid Ali Siddique; Ruidong Fan; Yanjiang Liu; Esmat F. Ali; Manish Kumar; Xing Yang; Jörg Rinklebe; Xiaoyulong Chen; et al. (Science of The Total Environment, 2024)

Emerging trends to replace pesticides with nanomaterials: Recent experiences and future perspectives for ecofriendly environment - Hong Wang; Muhammad Jafir; Muhammad Irfan; Tanveer Ahmad; Muhammad Zia-ur-Rehman; Muhammad Usman; Muhammad Rizwan; Yousef Alhaj Hamoud; Hiba Shaghaleh (Journal of Environmental Management, 2024)

Correction: Zinc Nanoparticles for Enhancing Plant Tolerance to Abiotic Stress: A Bibliometric Analysis and Review - Muhammad Jafir; Aqsa Khan; Adeel Ahmad; Khalid Hussain; Muhammad Zia ur Rehman; Samina Jam Nazeer Ahmad; Muhammad Irfan; Muhammad Azeem Sabir; Tanveer Hussain Khan; Usman Zulfiqar (Journal of Soil Science and Plant Nutrition, 2024)

Zinc Nanoparticles for Enhancing Plant Tolerance to Abiotic Stress: A Bibliometric Analysis and Review - Muhammad Jafir; Aqsa Khan; Adeel Ahmad; Khalid Hussain; Muhammad Zia ur Rehman; Samina Jam Nazeer Ahmad; Muhammad Irfan; Muhammad Azeem Sabir; Tanveer Hussain Khan; Usman Zulfiqar (Journal of Soil Science and Plant Nutrition, 2024)

Drought stress in sorghum: physiological tools, breeding technology, Omics approaches and Genomic-assisted breeding -A review - Waqas Liaqat; Muhammad Tanveer Altaf; Celaleddin Barutçular; Heba I. Mohamed; Zain Ali; Muhammad Owais Khan (Journal of Soil Science and Plant Nutrition, 2024)

Comparative Assessment of Bioactive Compounds, Fruit Quality Attributes and Sugar Profiling in Early Maturing Table Grape (Vitis Vinifera L.) Cultivars from Pothohar, Pakistan - Muhammad Tahir Akram; Rashad Qadri; Muhammad Azam Khan; Arif Atak; Mehwish Liaquat; Tanveer Hussain; Muhammad Mumtaz Khan; Muhammad Azam; Mahmood ul Hasan (Applied Fruit Science, 2024)

RETRACTED ARTICLE: Multifaceted role of TRIM21 in inflammation - Sana Tanveer; Ali Afzal; Zaman Gul; Hanan Afzal; Amara Noureen; Muhammad Sharif; Muhammad Babar Khawar (Biologia Futura, 2024)

Local-scale integrated seismic risk assessment using satellite data and field information in Northern Pakistan - Tanveer Ahmed; Khaista Rehman; Muhammad Shafique; Nisar Ali Shah; Muhammad Waqar Azeem (Stochastic Environmental Research and Risk Assessment, 2024)

Evaluating the Effect of pH, Temperature and Concentration on Antioxidant and Antibacterial Potential of Spectroscopically, Spectrophotometrically and Microscopically Characterized Mentha Spicata Capped Silver Nanoparticles - Tahreem Tanveer; Shaukat Ali; Nazish Mazhar Ali; Muhammad Adeel Farooq; Muhammad Summer; Ali Hassan; Fareha Ali; Muhammad Irfan; Lubna Kanwal; Hafsa Shahzad; Rahila Islam (Journal of Fluorescence, 2024)

New insights for simultaneous nutrient removal enhancement and greenhouse gas emissions reduction of constructed wetland by optimizing its redox environment through manganese oxide addition - Mingde Ji; Xue Zhang; Jiayang Heng; Muhammad Tanveer; Jian Zhang; Zizhang Guo; Zhen Hu (Water Research, 2024)

Phytoremediation of heavy metal-contaminated soil of Lyari River using bioenergy crops - Musarrat Ramzan; Saira Sarwar; Muhammad Zaheer Ahmad; Rifat Zubair Ahmed; Tanveer Hussain; Iqtidar Hussain (South African Journal of Botany, 2024)

Biochar: Black Gold for Sustainable Agriculture and Fortification Against Plant Pathogens—A Review - Usman Arshad; Muhammad Tanveer Altaf; Waqas Liaqat; Muhammad Ali; Muhammad Nadeem Shah; Muhammad Jabran; Muhammad Amjad Ali (Journal of Crop Health, 2024)

Leading report of molecular prevalence of tick borne Anaplasma marginale and Theileria ovis in yaks (Bos grunniens) from Pakistan - Muqaddas Nawaz; Rehmat Ullah; Zia Ur Rehman; Muhammad Naeem; Afshan Khan; Mohammed Bourhia; Muhammad Mudassir Sohail; Takbir Ali; Adil Khan; Tanveer Hussain; Furhan Iqbal (Archives of Microbiology, 2024)

Effect of multi-strain probiotics on the growth, hematological profile, blood biochemistry, antioxidant capacity, and physiological responses of Clarias batrachus fingerlings - Ayesha Tanveer; Noor Khan; Mahroze Fatima; Wazir Ali; Sadia Nazir; Sheeza Bano; Muhammad Asghar (Aquaculture International, 2024)

Enhancing the Quality and Fruit Yield of Sweet Cherry (Prunus Avium) Cultivars by Foliar Application of Boron - Muhammad Sajid; Abdul Basit; Syed Tanveer Shah; Ayesha Khan; Izhar Ullah; Muhammad Bilal; Muhammad Suleman Khan; Waleed Khan (Applied Fruit Science, 2024)

Sorghum: a Star Crop to Combat Abiotic Stresses, Food Insecurity, and Hunger Under a Changing Climate: a Review - Waqas Liaqat; Muhammad Tanveer Altaf; Celaleddin Barutçular; Heba I. Mohamed; Haseeb Ahmad; Muhammad Faheem Jan; Ehtisham Hassan Khan (Journal of Soil Science and Plant Nutrition, 2024)

Ultraviolet-B radiation in relation to agriculture in the context of climate change: a review - Waqas Liaqat; Muhammad Tanveer Altaf; Celaleddin Barutçular; Hira Nawaz; Izhar Ullah; Abdul Basit; Heba I. Mohamed (Cereal Research Communications, 2024)

Caring for the environment. How do deforestation, agricultural land, and urbanization degrade the environment? Fresh insight through the ARDL approach - Arsalan Tanveer; Huaming Song; Muhammad Faheem; Abdul Daud (Environment, Development and Sustainability, 2024)

Do firms walk the talk when economic uncertainty is high? - Muhammad Azeem Qureshi; Ammar Ali Gull; Tanveer Ahsan; Muhammad Ansar Majeed (Journal of Cleaner Production, 2024)

Mapping the link between CSR and sustainability performance through GHRM practices in hotel industry - Muhammad Imran Tanveer; Mohd Yusoff Yusliza; Abdul Hafaz Ngah; Muhammad Asif Khan Khan (Journal of Cleaner Production, 2023)

Is constructed wetlands carbon source or carbon sink? Case analysis based on life cycle carbon emission accounting - Shuo Wang; Xiaokang Li; Mingde Ji; Jian Zhang; Muhammad Tanveer; Zhen Hu (Bioresource Technology, 2023)

Nanotechnology: an Integrated Approach Towards Agriculture Production and Environmental Stress Tolerance in Plants - Izhar Ullah; Muhammad Danish Toor; Abdul Basit; Heba I. Mohamed; Mohammed Gamal; Nouraiz Ahmed Tanveer; Syed Tanveer Shah (Water, Air, & Soil Pollution, 2023)

Evaluating the influence of green growth, institutional quality and financial inclusion on financial stability: evidence by sustainable finance theory - Muhammad Sajid; Muhammad Akbar Ali Ansari; Arsalan Tanveer; Muhammad Faheem; Asim Waseem (Environmental Science and Pollution Research, 2023)

Guiding the optimization of membraneless microfluidic fuel cells via explainable artificial intelligence: Comparative analyses of multiple machine learning models and investigation of key operating parameters - Dang Dinh Nguyen; Muhammad Tanveer; Hang-Nga Mai; Thinh Quy Duc Pham; Haroon Khan; Cheol Woo Park; Gyu Man Kim (Fuel, 2023)

Enhancement of photocatalytic activity of Ba-doped CoO for degradation of Emamectin benzoate in aqueous solution - Huma Khalid; Atta ul Haq; Syed Ali Raza Naqvi; Muhammad Usman; Tanveer Hussain Bokhari (Environmental Monitoring and Assessment, 2023)

A Recent Digitalization in Recycling Industry Attaining Ecological Sustainability: A Comprehensive Outlook and Future Trend - Syed Abdul Rehman Khan; Muhammad Umar; Zhang Yu; Muhammad Tanveer Nawaz (Environmental Science and Pollution Research, 2023)

Assessment of essential and toxic elemental concentrations in tumor and non-tumor tissues with risk of colorectal carcinoma in Pakistan - Muhammad Abdul Qayyum; Tahir Farooq; Aqsa Baig; Tanveer Hussain Bokhari; Muhammad Naveed Anjum; Mian Habib-ur-Rahman Mahmood; Ahmad Raza Ashraf; Khawaja Muddassir; Muhammad Ahmad (Journal of Trace Elements in Medicine and Biology, 2023)

Modelling Electricity Consumption During the COVID19 Pandemic: Datasets, Models, Results and a Research Agenda - Zulfiqar Ahmad Khan; Tanveer Hussain; Amin Ullah; Waseem Ullah; Javier Del Ser; Khan Muhammad; Muhammad Sajjad; Sung Wook Baik (Energy and Buildings, 2023)

Synthesis of Elemental- and Nano-sulfur-enriched Bio-organic Phosphate Composites, and Their Impact on Nutrients Bioavailability and Maize Growth - Ayesha Shakoor; Ghulam Jilani; Tanveer Iqbal; Imran Mahmood; Tajwar Alam; Muhammad Asif Ali; Syed Shahid Hussain Shah; Rizwan Ahmad (Journal of Soil Science and Plant Nutrition, 2023)

Microplastics: unraveling the signaling pathways involved in reproductive health - Muhammad Tanveer; Nimra Mansha; Afzal Nimra; Muhammad Babar Khawar; Ali Afzal; Hanan Afzal; Muhammad Farooq; Sadia Ehsan; Rabbia Rana; Sara Shahzaman (Environmental Science and Pollution Research, 2023)

iPBS-retrotransposons variations: DNA fingerprinting and the evaluation of genetic diversity and population structure in international cowpea germplasm - Faheem Shehzad Baloch; Muhammad Tanveer Altaf; Mehmet Bedir; Muhammad Azhar Nadeem; Muhammed Tatar; Tolga Karaköy; Muhammad Aasim (Genetic Resources and Crop Evolution, 2023)

Health risk assessment and bioaccumulation of potentially toxic metals from water, soil, and forages near coal mines of district Chakwal, Punjab, Pakistan - Nida Zainab; Shehzad Mehmood; Amna Shafiq-ur-Rehman; Adeela Munir; Zafar Iqbal Tanveer; Zaib Un Nisa; Muhammad Imran; Muhammad Tariq Javed; Hassan Javed Chaudhary (Environmental Geochemistry and Health, 2023)

Exploration of the bioenergy potential of Dactyloctenium aegyptium through pyrolysis, kinetics, and thermodynamic parameters to produce clean fuels and biochemicals - Hesham Alhumade; Omar S. Alayed; Muhammad Waqas Iqbal; Ayesha Shahid; Tanveer Iqbal; Muhammad Sajjad Ahmad; Ali Elkamel; Yusuf Al-Turki; Muhammad Aamer Mehmood; Ghulam Abbas Ashraf (Fuel, 2023)

Bioenergy potential of Saccharum bengalense through pyrolysis, reaction kinetics, TG-FTIR-GCMS analysis of pyrolysis products, and validation of the pyrolysis data through machine learning - Azeem Asghar; Chen-Guang Liu; Imtiaz Ali; Aqib Zafar Khan; Hui Zhu; Ning Wang; Muhammad Nawaz; Tanveer A. Tabish; Muhammad Aamer Mehmood; Raqiqa Tur Rasool (Chemical Engineering Journal, 2023)

Artificial neural network and decision tree facilitated prediction and validation of cytokinin-auxin induced in vitro organogenesis of sorghum (Sorghum bicolor L.) - Muhammad Aasim; Seyid Amjad Ali; Muhammad Tanveer Altaf; Amjad Ali; Muhammad Azhar Nadeem; Faheem Shahzad Baloch (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Exploring the genetic diversity and population structure of upland cotton germplasm by iPBS-retrotransposons markers - Nurettin Baran; Flavien Shimira; Muhammad Azhar nadeem; Muhammad Tanveer altaf; Mehtap andirman; Faheem Shehzad Baloch; Mefhar Gültekin Temiz (Molecular Biology Reports, 2023)

Eco-friendly microwave assisted sustainable coloration of silk and wool fabric with Acid Blue 07 dye - Shahid Adeel; Hira Akram; Muhammad Usman; Tanveer Hussain Bokhari; Muhammad Aftab; Meral Ozomay (Environmental Science and Pollution Research, 2023)

Functional characterization of transcriptional activator gene SIARRI in tomato reveals its role in fruit growth and ripening - Muhammad Fahad; Muhammad Tanveer Altaf; Amna Jamil; Abdul Basit; Muhammad Mudassir Aslam; Waqas Liaqat; Muhammad Nadeem Shah; Izhar Ullah; Heba I. Mohamed (Transgenic Research, 2023)

Impact of eco-friendly chemical pretreatment on physicochemical and surface mechanical properties of sustainable lignocellulosic agricultural waste - Muhammad Sulaiman; Fahad Ali Rabbani; Tanveer Iqbal; Mohsin Ali Kazmi; Saima Yasin; M.A. Mujtaba; M.A. Kalam; Fares Almomani (Algal Research, 2023)

Nanoparticles assisted regulation of oxidative stress and antioxidant enzyme system in plants under salt stress: A review - Muhammad Zia-ur-Rehman; Sidra Anayatullah; Effa Irfan; Syed Makhdoom Hussain; Muhammad Rizwan; Muhammad Irfan Sohail; Muhammad Jafir; Tanveer Ahmad; Muhammad Usman; Hesham F. Alharby (Chemosphere, 2023)

A review of particulate pollution over Himalaya region: Characteristics and salient factors contributing ambient PM pollution - Muhammad Azher Hassan; Tariq Mehmood; Junjie Liu; Xiaosan Luo; Xinghua Li; Mohsin Tanveer; Muhammad Faheem; Awais Shakoor; Afzal Ahmed Dar; Muhammad Abid (Atmospheric Environment, 2023)

Zinc oxide nanoparticles mediated biostimulant impact on cadmium detoxification and in silico analysis of zinc oxide-cadmium networks in Zea mays L. regulome - Yashfa Tanveer; Saman Jahangir; Zafar Abbas Shah; Humaira Yasmin; Asia Nosheen; Muhammad Nadeem Hassan; Noshin Illyas; Andrzej Bajguz; Mohamed A. El-Sheikh; Parvaiz Ahmad (Environmental Pollution, 2023)

Application of RNAi technology: a novel approach to navigate abiotic stresses - Izhar Ullah; Ehab A. R. Kamel; Syed Tanveer Shah; Abdul Basit; Heba I. Mohamed; Muhammad Sajid (Molecular Biology Reports, 2022)

Waste management and green technology: future trends in circular economy leading towards environmental sustainability - Muhammad Tanveer; Syed Abdul Rehman Khan; Muhammad Umar; Zhang Yu; Muhammad Jawad Sajid; Ikram Ul Haq (Environmental Science and Pollution Research, 2022)

The paradigms of transport energy consumption and technological innovation as a panacea for sustainable environment: is there any asymmetric association? - Arsalan Tanveer; Huaming Song; Muhammad Faheem; Abdul Daud (Environmental Science and Pollution Research, 2022)

Eco-friendly acid dyeing of silk and wool fabrics using Acid Violet 49 dye - Muhammad Usama Shabbir; Shahid Adeel; Tanveer Hussain Bokhari; Muhammad Usman; Muhammad Kaleem Khosa; Tanvir Ahmad; Asma Inayat (Environmental Science and Pollution Research, 2022)

Thermal Plasticity and Cotton Production Enhancing Attributes of Phosphate-Solubilizing Bacteria from Cotton Rhizosphere - Suleman Haider Shah; Muhammad Baqir Hussain; Zahir Ahmad Zahir; Tanveer Ul Haq; Amar Matloob (Journal of Soil Science and Plant Nutrition, 2022)

Correction to: Sustainable supply chain management and green technologies: a bibliometric review of literature - Zhang Yu; Muhammad Waqas; Muhammad Tabish; Muhammad Tanveer; Ikram Ul Haq; Syed Abdul Rehman Khan (Environmental Science and Pollution Research, 2022)

Sustainable supply chain management and green technologies: a bibliometric review of literature - Zhang Yu; Muhammad Waqas; Muhammad Tabish; Muhammad Tanveer; Ikram Ul Haq; Syed Abdul Rehman Khan (Environmental Science and Pollution Research, 2022)

Do investors penalize the firms disclosing higher environmental performance? a cross cultural evidence - Muhammad Azeem Qureshi; Tanveer Ahsan (Environmental Science and Pollution Research, 2022)
Climate change discourse integrates 3Ps – people, planet, and profit. However, we do not find any empirical study that integrates 3Ps. Therefore, using a large global panel dataset from 46 countries, this study intends to fill this gap by providing empirical evidence about investors’ value proposition of corporate climate performance in different cultural environments. The results show that Hofstede’s cultural dimensions affect corporate climate performance and its market pricing. We find that in cultures with high power distance, low individualism, high masculinity, high uncertainty avoidance, high long-term orientation, and high restraint, the investors generally penalize the firms disclosing higher environmental performance. Strangely enough, corporate waste production is universally value irrelevant. Our results indicate some policy implications.

Occurrence of Microplastics and Heavy Metals in Aquatic and Agroecosystem: A Case Study - Tanveer Ahmad; Muhammad Amjad; Qumer Iqbal; Asmat Batool; Anam Noor; Muhammad Jafir; Hammad Hussain; Muhammad Irfan (Bulletin of Environmental Contamination and Toxicology, 2022)

Assessment of genetic diversity among 131 safflower (Carthamus tinctorius L.) accessions using peroxidase gene polymorphism (POGP) markers - Mehtap Yildiz; Muhammad Tanveer Altaf; Faheem Shehzad Baloch; Metin Koçak; Gökhan Sadık; Cansu Kuzğun; Muhammad Azhar Nadeem; Fawad Ali; Mehmet Bedir; Murat Tunçtürk (Molecular Biology Reports, 2022)

MiRNA fine tuning for crop improvement: using advance computational models and biotechnological tools - Asad Abbas; Adnan Noor Shah; Mohsin Tanveer; Waseem Ahmed; Anis Ali Shah; Sajid Fiaz; Muhammad Mohsin Waqas; Sami Ullah (Molecular Biology Reports, 2022)

Reducing nutrient uptake in okra weeds by suppressing their population through alligator weed compost mulch for better pod yield and quality - Asif Tanveer; Muhammad Sarwar; Muhammad Shahbaz Asghar; Muhammad Farrukh Saleem; Hamza Maqsood; Basharat Ali; Muhammad Kashif Munir; Muhammad Arshad; Rao Muhammad Ikram; Nabeel Ahmad Ikram; Muhammad Rizwan (Arabian Journal of Geosciences, 2022)

Impact of different nitrogen management options and weed competition periods on weed dynamics, productivity, and profitability of bread wheat - Muhammad Saqib; Abdul Khaliq; Asif Tanveer; Tariq Aziz (Arabian Journal of Geosciences, 2022)

Applicability of inter-primer binding site iPBS- retrotransposon marker system for the assessment of genetic diversity and population structure of Peruvian rosewood (Aniba rosaeodora Ducke) germplasm - Faheem Shehzad Baloch; Stalin Juan Vasquez Guizado; Muhammad Tanveer Altaf; Ilker Yüce; Yeter Çilesiz; Mehmet Bedir; Muhammad Azhar Nadeem; Rustu Hatipoglu; Juan Carlos Castro Gómez (Molecular Biology Reports, 2022)

Validation of environmental Philips curve in Pakistan: a fresh insight through ARDL technique - Arsalan Tanveer; Huaming Song; Muhammad Faheem; Imran Sharif Chaudhry (Environmental Science and Pollution Research, 2022)

Impact of globalization, institutional quality, economic growth, electricity and renewable energy consumption on Carbon Dioxide Emission in OECD countries - Huimin Cao; Muhammad Kamran Khan; Abdul Rehman; Vishal Dagar; Bahareh Oryani; Arifa Tanveer (Environmental Science and Pollution Research, 2022)

Biochar and slow-releasing nitrogen fertilizers improved growth, nitrogen use, yield, and fiber quality of cotton under arid climatic conditions - Sobia Manzoor; Muhammad Habib-ur-Rahman; Ghulam Haider; Iqra Ghafoor; Saeed Ahmad; Muhammad Afzal; Fahim Nawaz; Rashid Iqbal; Mubashra Yasin; Tanveer-ul-Haq; Subhan Danish; Abdul Ghaffar (Environmental Science and Pollution Research, 2022)
The efficiency of nitrogenous fertilizers in South Asia is on a declining trajectory due to increased losses. Biochar (BC) and slow-releasing nitrogen fertilizers (SRNF) have been found to improve nitrogen use efficiency (NUE) in certain cases. However, field-scale studies to explore the potential of BC and SRNF in south Asian arid climate are lacking. Here we conducted a field experiment in the arid environment to demonstrate the response of BC and SRNF on cotton growth and yield quality. The treatments were comprised of two factors, (A) nitrogen sources, (i) simple urea, (ii)neem-coated urea, (iii)sulfur-coated urea, (iv) bacterial coated urea, and cotton stalks biochar impregnated with simple urea, and (B) nitrogen application rates, N 1 =160 kg ha -1 , N 2 = 120 kg ha -1 , and N 3 = 80 kg ha -1 . Different SRNF differentially affected cotton growth, morphological and physiological attributes, and seed cotton yield (SCY). The bacterial coated urea at the highest rate of N application (160 kg ha -1 ) resulted in a higher net leaf photosynthetic rate (32.8 μmol m -2 s -1 ), leaf transpiration rate (8.10 mmol s -1 ), and stomatal conductance (0.502 mol m -2 s -1 ), while leaf area index (LAI), crop growth rate (CGR), and seed cotton yield (4513 kg ha -1 ) were increased by bacterial coated urea at 120 kg ha -1 than simple urea. However, low rate N application (80 kg ha -1 ) of bacterial coated urea showed higher nitrogen use efficiency (39.6 kg SCY kg -1 N). The fiber quality (fiber length, fiber strength, ginning outturn, fiber index, and seed index) was also increased with the high N application rates than N2 and N3 application. To summarize, the bacterial coated urea with recommended N (160 kg ha -1 ) and 75% of recommended N application (120 kg ha -1 ) may be recommended for farmers in the arid climatic conditions of Punjab to enhance the seed cotton yield, thereby reducing nitrogen losses.

Investigation of antifungal response of NiO and copper-doped NiO thin films against Aspergillus niger and Macrophomina phaseolina fungi - Muzamil Aftab; Muhammad Zakria Butt; Dilawar Ali; Zille Huma Aftab; Muhammad Usman Tanveer; Bakhtawar Fayyaz (Environmental Science and Pollution Research, 2022)

Unveiling the asymmetric impact of energy consumption on environmental mitigation in the manufacturing sector of Pakistan - Arsalan Tanveer; Huaming Song; Muhammad Faheem; Abdul Daud; Saira Naseer (Environmental Science and Pollution Research, 2021)

Comparative study of flash flood in ungauged watershed with special emphasizing on rough set theory for handling the missing hydrological values - Muhammad Waseem Boota; Chaode Yan; Tanveer Abbas; Ziwei Li; Ming Dou; Ayesha Yousaf (Natural Hazards, 2021)

Silver nanoparticles biosynthesized from secondary metabolite producing marine actinobacteria and evaluation of their biomedical potential - Ashia Alam; Faouzia Tanveer; Ali Talha Khalil; Tanzeel Zohra; Saleh Khamlich; Muhammad Masroor Alam; Muhammad Salman; Muhammad Ali; Aamer Ikram; Zabta Khan Shinwari; Malik Maaza (Antonie van Leeuwenhoek, 2021)

Sulfate-Based Fertilizers Regulate Nutrient Uptake, Photosynthetic Gas Exchange, and Enzymatic Antioxidants to Increase Sunflower Growth and Yield Under Drought Stress - Bilal Ahamid Shafiq; Fahim Nawaz; Sadia Majeed; Muhammad Aurangzaib; Abdullah Al Mamun; Muhammad Ahsan; Khawaja Shafique Ahmad; Muhammad Asif Shehzad; Muqarrab Ali; Sarfraz Hashim; Tanveer ul Haq (Journal of Soil Science and Plant Nutrition, 2021)
The challenging impact of drought to agricultural productivity requires the adoption of mitigation strategies with a better understanding of underlying mechanisms responsible for drought tolerance. The present study aimed at investigating the effects of sulfur-based fertilizers on mitigation of drought stress in sunflower. Sulfate-containing fertilizers, viz., ammonium sulfate, zinc sulfate, magnesium sulfate, potassium sulfate, and gypsum, were initially evaluated at two different rates (10 and 20 mg kg −1 soil equivalent to 20 and 40 kg ha −1 , respectively) for nutrient uptake and growth-promoting traits in sunflower seedlings (cv. Hysun-33). The best performing fertilizer (gypsum) was then selected to evaluate the response of sunflower under drought stress imposed at flowering stage for three weeks (25–30% water holding capacity). Results indicated significant amelioration of drought stress with higher activity of photosynthetic apparatus, upregulation of antioxidative enzymes, and increased achene yield by gypsum application. In comparison to control, gypsum-treated plants (20 mg kg −1 soil) exhibited higher water status (32%), leaf photosynthetic rate (29%), transpiration rate (67%), and stomatal conductance (118%) under drought stress. The antioxidant enzyme activities of catalase, guaiacol peroxidase, and superoxide dismutase were also increased by 67%, 62%, and 126%, respectively, resulting in higher achene yield (19%) under water-deficit conditions. This study indicates that the application of sulfur-based fertilizers (gypsum) can be used to induce drought tolerance and obtain high sunflower yields under drought stress, and furthermore, it is a cost-effective strategy resulting in high benefit–cost ratio with respect to no gypsum application.

Association between meteorological indicators and COVID-19 pandemic in Pakistan - Ali Raza; Muhammad Tariq Iqbal Khan; Qamar Ali; Tanveer Hussain; Saadia Narjis (Environmental Science and Pollution Research, 2021)

Genome sequence analysis and bioactivity profiling of marine-derived actinobacteria, Brevibacterium luteolum, and Cellulosimicrobium funkei - Faouzia Tanveer; Muhammad Shehroz; Muhammad Ali; Yunying Xie; Rashda Abbasi; Zabta Khan Shinwari; Azra Yasmin (Archives of Microbiology, 2021)

Foliar Applied Thiourea Improved Physiological Traits and Yield of Camelina and Canola Under Normal and Heat Stress Conditions - Muhammad Ahmad; Ejaz Ahmad Waraich; Asif Tanveer; Muhammad Anwar-ul-Haq (Journal of Soil Science and Plant Nutrition, 2021)

Mitigating Drought Stress in Sunflower (Helianthus annuus L.) Through Exogenous Application of β-Aminobutyric Acid - Allah Wasaya; Tanveer Abbas; Tauqeer Ahmad Yasir; Naeem Sarwar; Ahsan Aziz; Muhammad Mansoor Javaid; Sheeraz Akram (Journal of Soil Science and Plant Nutrition, 2021)

Estimation of data-driven streamflow predicting models using machine learning methods - Tanveer Ahmed Siddiqi; Saima Ashraf; Sadiq Ali Khan; Muhammad Jawed Iqbal (Arabian Journal of Geosciences, 2021)

Performance evaluation of participatory irrigation management as an alternative to a state‐managed irrigation system* - Sabir Hussain; Mudasser Muneer Khan; Muhammad Shoaib; Ali Raza; Syyed Adnan Raheel Shah; Tanveer Ahmed Khan; Sher Khan (Irrigation and Drainage, 2021)
The Lower Bari Doab Canal (LBDC) system is one of the large old irrigation systems in Punjab, Pakistan. To overcome problems of water distribution and management in conventional state‐managed irrigation, a participatory irrigation management (PIM) system was introduced in the LBDC command area in 2012. From the very large system of the LBDC, 20 different kinds of distributaries were selected in this study as representatives for evaluating performance of the new system. The primary data were gathered through questionnaires and by interviewing farmers, whereas the secondary data were gathered from the related offices of the Punjab Irrigation Department. The analysis of collected data illustrates that water service deliveries (WSDs) were poor even after implementation of PIM. The research shows that under administration of both systems, efficiency regarding provision of water seemed to be poor. The outcomes show that with the passage of time, recovery ( abiana ) decreased after implementation of the PIM system but the financial sustainability of PIM has improved compared to state administration. Finally, the current study recommends institutional reforms in PIM and comprehensive work on educating the farmers about their role in PIM as a mandatory component for improving efficiency of the PIM system.

Spicing up gastrointestinal health with dietary essential oils - Mahwish Tanveer; Charles Wagner; Muhammad Ikram ul Haq; Nilton C. Ribeiro; Thriumurugan Rathinasabapathy; Masood Sadiq Butt; Aamir Shehzad; Slavko Komarnytsky (Phytochemistry Reviews, 2020)

Isolation and genetic characterization of virulent strains of avian paramyxovirus-1 from multiple avian species in Azad Jammu and Kashmir 2017–2018 - Abid Hussain; Abdul Wajid; Safa Ather; Kashaf Alyas; Muhammad Awais; Muhammad Rizwan Khan; Tanveer Hussain; Masroor Ellahi Babar (Brazilian Journal of Microbiology, 2020)

Glycinebetaine alleviates the chromium toxicity in Brassica oleracea L. by suppressing oxidative stress and modulating the plant morphology and photosynthetic attributes - Rehan Ahmad; Shafaqat Ali; Muhammad Abid; Muhammad Rizwan; Basharat Ali; Asif Tanveer; Irfan Ahmad; Muhammad Azam; Muhammad Awais Ghani (Environmental Science and Pollution Research, 2020)

Impact of biochar prepared from leaves of Populous euphratica on soil microbial activity and mung bean (Vigna radiata) growth - Muhammad Akmal; Tanveer Ahmed Gondal; Khalid Saifullah Khan; Qaiser Hussain; Mukhtar Ahmad; Muhammad Subtain Abbas; Hafeez Ullah Rafa; Shahab Ahmad Khosa (Arabian Journal of Geosciences, 2019)

Correction to: Preparation, optimization and pharmacological evaluation of 99mTc-4-hydroxy-3-(2-hydroxy-3-methoxybenzylideneamino) benzoic acid complex: as a novel potential radiopharmaceutical agent with hepatobiliary excretion - Muhammad Usman Akbar; Tanveer Hussain Bokhari; Samina Roohi; Khalid Mahmood Zia; Muhammad Razeen Ahmad; Saira Hina; Muhammad Sohaib (Molecular Biology Reports, 2018)

Quantifying climate internal variability using an hourly ensemble generator over South Korea - Jongho Kim; Muhammad Ejaz Tanveer; Deg-Hyo Bae (Stochastic Environmental Research and Risk Assessment, 2018)

Behavioral activity patterns of adult and juvenile Greater Flamingos (Phoenicopterus roseus) with alteration of climatic pattern at Uchalli Lake, Punjab, Pakistan - Shabana Naz; Arnab Tanveer; Muhammad Abrar; Asma Ashraf (Environmental Science and Pollution Research, 2018)

Synthesis of Symmetric Bridged Bis-Pyrazolone Based Metal Complex Acid Dyes and their Applications on Leather - Muhammad Ayaz; Muhammad Ayaz; Farman Ali; Aamer Saeed; Asma Khurshid; Ghulam Shabir; Tanveer Ahmad; Syed Asad Raza Kazmi; Hassan Ali Khan (Journal of Fluorescence, 2018)

Identification of phytotoxins in different plant parts of Brassica napus and their influence on mung bean - Azhar Mehmood; Muhammad Naeem; Farhan Khalid; Yousaf Saeed; Tasawer Abbas; Khawar Jabran; Muhammad Aqeel Sarwar; Asif Tanveer; Muhammad Mansoor Javaid (Environmental Science and Pollution Research, 2018)

Physiological responses of wheat to drought stress and its mitigation approaches - Zahoor Ahmad; Ejaz Ahmad Waraich; Sajjad Akhtar; Shazia Anjum; Tanveer Ahmad; Wajid Mahboob; Osama Bin Abdul Hafeez; Terence Tapera; Maryke Labuschagne; Muhammad Rizwan (Acta Physiologiae Plantarum, 2018)

Augmentation with potential endophytes enhances phytostabilization of Cr in contaminated soil - Muhammad T. Ahsan; Muhammad Najam-ul-haq; Abdul Saeed; Tanveer Mustafa; Muhammad Afzal (Environmental Science and Pollution Research, 2018)

Soil compaction effects on soil health and cropproductivity: an overview - Adnan Noor Shah; Mohsin Tanveer; Babar Shahzad; Guozheng Yang; Shah Fahad; Saif Ali; Muhammad Adnan Bukhari; Shahbaz Atta Tung; Abdul Hafeez; Biangkham Souliyanonh (Environmental Science and Pollution Research, 2017)

Nitrogen fertilization and conservation tillage: a review on growth, yield, and greenhouse gas emissions in cotton - Adnan Noor Shah; Javaid Iqbal; Mohsin Tanveer; Guozheng Yang; Waseem Hassan; Shah Fahad; Muhammad Yousaf; Yingying Wu (Environmental Science and Pollution Research, 2017)

Aluminum and Chromium Toxicity in Maize: Implications for Agronomic Attributes, Net Photosynthesis, Physio-Biochemical Oscillations, and Metal Accumulation in Different Plant Parts - Shakeel Ahmad Anjum; Umair Ashraf; Imran Khan; Mohsin Tanveer; Muhammad Farrukh Saleem; Longchang Wang (Water, Air, & Soil Pollution, 2016)

Allelopathic potential of oil seed crops in production of crops: a review - Adnan Noor Shah; Javaid Iqbal; Abid Ullah; Guozheng Yang; Muhammad Yousaf; Shah Fahad; Mohsin Tanveer; Waseem Hassan; Shahbaz Atta Tung; Leishan Wang; Aziz Khan; Yingying Wu (Environmental Science and Pollution Research, 2016)

Osmoregulation and antioxidant production in maize under combined cadmium and arsenic stress - Shakeel Ahmad Anjum; Mohsin Tanveer; Saddam Hussain; Babar Shahzad; Umair Ashraf; Shah Fahad; Waseem Hassan; Saad Jan; Imran Khan; Muhammad Farrukh Saleem; Ali Ahsan Bajwa; Longchang Wang; et al. (Environmental Science and Pollution Research, 2016)

Tree species as a potential source of bio-herbicides for controlling Parthenium hysterophorus L. - Muhammad Ehsan Safdar; Asif Tanveer; Abdul Khaliq; Muhammad Shahbaz Naeem; Salman Ahmad (Natural Product Research, 2013)

DNA typing of Pakistani cattle breeds Tharparkar and Red Sindhi by microsatellite markers - Amber Azam; Masroor Ellahi Babar; Sehrish Firyal; Aftab Ahmad Anjum; Nabeela Akhtar; Muhammad Asif; Tanveer Hussain (Molecular Biology Reports, 2012)

Investigating the concurrent presence of HCV in serum, oral fluid and urine samples from chronic HCV patients in Faisalabad, Pakistan - Muhammad Shafique; Nasir Ahmad; Fazli R. Awan; Tanveer Mustafa; Mujib Ullah; Javed A. Qureshi (Archives of Virology, 2009)

Relationship among acidophilic bacteria from diverse environments as determined by randomly amplified polymorphic DNA analysis (RAPD) - Tanveer Akbar; Kalsoom Akhtar; Muhammad A. Ghauri; Munir A. Anwar; Moazur Rehman; Mehboobur Rehman; Yusuf Zafar; Ahmad M. Khalid (World Journal of Microbiology and Biotechnology, 2005)